2018
DOI: 10.1016/j.vacuum.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Homo-epitaxial growth of single crystal diamond in the purified environment by active O atoms

Abstract: The pure oxygen was introduced into the growth environment of the single crystal diamond with different contents, and the growth characteristics of single crystal diamond and the reaction dynamics in the plasma were studied in detail. As the ratio of O 2 to H 2 is up to 1.5%, the unique shaped etching pits with eight symmetric crystallographic planes appear. Optical emission spectra present typical characteristic radicals in the O 2 incorporated growth environment. With amount of O 2 increases, the growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Among the various roles of oxygen addition, the strongest enhancement is the gas phase reactions and preferential etching of non-diamond bonded carbon. However, a high ratio of O 2 addition could increase the etching rate of the diamond phase, which would reduce the growth rate and had an adverse effect on smoothness [22,25], as shown in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various roles of oxygen addition, the strongest enhancement is the gas phase reactions and preferential etching of non-diamond bonded carbon. However, a high ratio of O 2 addition could increase the etching rate of the diamond phase, which would reduce the growth rate and had an adverse effect on smoothness [22,25], as shown in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 99%
“…Thus different gas system and deposition parameters determine the characteristics of synthetic UNCDs. In addition to the catalytic function of nitrogen for N-UNCD synthesizing [19][20][21], the existence of oxygen in plasma system can effectively improve the crystallinity as a cleaner and surface smoothness of synthesized diamond [22]. On the other hand, graphitization is easier to form in H-poor system because the C 2 radical reaction acts as the main growth mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] For example, Issaoui et al [16] have studied the effect of oxygen on the heavily boron-doped diamond and shown that the obtained films exhibit high crystalline quality with adding a large amount of oxygen in gas phase. However, most of the prior literature focuses on the effect of oxygen on the properties (such as crystalline quality, [17,18] growth rate, [18,19] and electrical property [17,19] ) in heavily boron-doped diamond. The effect of oxygen on properties of moderately boron-doped diamond is lack of systematic research, especially effect of oxygen on regulation of acceptor concentration and donor concentration, and compensation of oxygen is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hexagonal boron nitride (h-BN), SiC, and diamond [1,2] are representatives of the third-generation wide-bandgap semiconductor materials. The h-BN is a white crystal, and its crystal structure is very similar to graphite, so the h-BN is also called "white graphite".…”
Section: Introductionmentioning
confidence: 99%